Latent infection of Vigna unguiculata with seed-borne bean common mosaic virus modulates plant growth and may contribute to mutualistic symbiosis between the virus and host plant - Hideki Takahashi; Nan Xu; Yoshinori Kanayama; Midori Tabara; Atsushi Takeda; Toshiyuki Fukuhara; Shuhei Miyashita (Frontiers in Microbiology)
In evaluating the germination and growth of the seed resources of 322 cultivars of cowpea (Vigna unguiculata), we found the development of yellow symptoms on ~50% of the cotyledons of 10 cultivars. RNA-Seq analysis of total RNA extracted from symptomatic cotyledons indicated that the 10 cultivars were infected with the bean common mosaic virus (Potyvirus phaseovulgaris, BCMV), which is a member of the family Potyviridae and able to seed-transmit to progeny plants. One of the BCMV isolates identified in the 10 cultivars was BCMV(Vu06), which was infected with cultivar #6. During the growth of BCMV(Vu06)-infected cowpea plants, there were no systemic symptoms in newly developing leaves, but the virus coat protein was detected in both leaves and flowers. Thus, the cowpea cultivar #6 plant was latently infected with BCMV(Vu06). There was no significant difference in the dry matter weight of the above-ground parts of the plant between BCMV(Vu06)-latently infected and non-infected plants. However, BCMV(Vu06)-latently infected plants had late flower and bud formation and longer life but slightly lower seed yield than the non-infected plants. The 1,000-seed weight and germination frequency of the seeds harvested from infected plants were the same as those of non-infected plants. Taken together, latent infection of cultivar #6 with BCMV(Vu6) modulates the balance between vegetative and reproductive plant growth and the longer lifespan of BCMV(Vu06)-latently infected plants may provide an advantage for its survivability over generations. BCMV(Vu06) and cowpea cultivar #6 might have established a mutual symbiotic relationship during their interaction.